Q: Multiply -9m(2m2 + 6m – 1)
A: When adding and subtracting polynomials, you can only combined like terms. This is not the case with multiplication. You can multiply unlike terms together.
-9m(2m2 + 6m – 1)
In this problem the whole quantity in the parentheses is being multiplied by -9m. So, -9m needs to multiply each term:
-9m(2m2 + 6m – 1) = -9m*2m2 + -9m*6m + -9m*-1
Now we need to clean up the expression on the right:
-9m*2m2 + -9m*6m + -9m*-1 ….
-9m*2m2 can be thought of as -9*m*2*m*m = -18m3
(multiply the coefficients together, and multiply the m’s together)
-9m*6m = -54m2
-9m*-1 = 9m
So, final answer cleans up like:
-9m(2m2 + 6m – 1) = -18m3 – 54m2 + 9m